The Decomposition Method of Surface Electromyographic Signals: A Novel Approach for Motor Unit Activity and Recruitment Description - Šádek, P; Otáhal, J (Physiological research, 2024)
This review aims to describe a novel method in the field of electromyography (EMG), established and improved upon in the last three decades that is able to observe specific parameters of muscle units (MUs). This concept is called the decomposition method, based on its ability to decompose a surface EMG signal to describe muscle activity on the level of individual muscle units in contrast to the level of the whole muscle, as is customary for regular surface electromyography. We provide a brief overview of its history, constituent parts regarding both hardware and software and possible applications. We also acknowledge the state of the research, regarding the background of the decomposition algorithm, the main software component responsible for identifying individual motor units and their parameters. As a result of the ability to describe the behavior of individual motor units during muscle contractions, key concepts in neuromuscular physiology have been put forward, pertaining to the hierarchy of MUs during their recruitment. Together with the recent application for cyclic contractions and gait, the decomposition method is beginning to open up wider possibilities of enquiry.
Keywords: algoritmy; Motor Neurons; Signal Processing, Computer-Assisted; motorické neurony; svalová kontrakce; kosterní svaly; počítačové zpracování signálu; Animals; Humans; Recruitment, Neurophysiological; lidé; Algorithms; zvířata; elektromyografie; recruitment (neurofyziologie); Muscle Contraction; Muscle, Skeletal; Electromyography